Synthesis of (−)-Pseudotabersonine, (−)-Pseudovincadifformine, and (+)-Coronaridine Enabled by Photoredox Catalysis in Flow - Beatty, Joel W. (J Am Chem Soc, 2014)
[Image: see text] Natural product modification with photoredox catalysis allows for mild, chemoselective access to a wide array of related structures in complex areas of chemical space, providing the possibility for novel structural motifs as well as useful quantities of less abundant congeners. While amine additives have been used extensively as stoichiometric electron donors for photocatalysis, the controlled modification of amine substrates through single-electron oxidation is ideal for the synthesis and modification of alkaloids. Here, we report the conversion of the amine (+)-catharanthine into the natural products (−)-pseudotabersonine, (−)-pseudovincadifformine, and (+)-coronaridine utilizing visible light photoredox catalysis.